Set Up for Failure: Pre-Existing Autoantibodies in Lung Transplant - McQuiston, Alexander; Emtiazjoo, Amir; Angel, Peggi; Machuca, Tiago; Christie, Jason; Atkinson, Carl (Frontiers in Immunology, 2021)
Lung transplant patients have the lowest long-term survival rates compared to other solid organ transplants. The complications after lung transplantation such as primary graft dysfunction (PGD) and ultimately chronic lung allograft dysfunction (CLAD) are the main reasons for this limited survival. In recent years, lung-specific autoantibodies that recognize non-HLA antigens have been hypothesized to contribute to graft injury and have been correlated with PGD, CLAD, and survival. Mounting evidence suggests that autoantibodies can develop during pulmonary disease progression before lung transplant, termed pre-existing autoantibodies, and may precipitate in allograft injury after transplantation. In this review, we summarize what is known about pulmonary disease autoantibodies, the relationship between pre-existing autoantibodies and lung transplantation, and potential mechanisms through which pre-existing autoantibodies contribute to graft injury and rejection.